Psychological and Pedagogical Features of the Construction of the Educational Process in the Study of Foreign (Oriental) Languages - Shoira Hamidovna, Abdullayeva; Dilafruz Rustamboyevna, Turayeva; Sayyora Rustamovna, Kamalova; Timur Sobirovich, Sattarov; Ra’no Anvarovna, Khaydarova; Aziza Asfandiyarovna, Shayusupova (International Journal of Psychosocial Rehabilitation, 2020)
Features of the style are studied in various types of life: educational, sports, and labor. The following types of styles are considered: cognitive, lifestyle, behavior style, individual activity style, individual self-regulation style, and individual emotional style. The relevance of the research topic “Psychological and Pedagogical Features of the Educational Process in the Study of Foreign (Oriental) Languages” selected for study is determined, on the one hand, by the modern requirements for studying this problem and, on the other, by the needs of the educational practice of universities. In the research process, we used the type of observation of the communication style according to the “Flanders System of Communication Analysis” and the 16-factor Kettell test. The aim of the study is to determine the socio-psychological characteristics of the style of activity of teachers of Tashkent State Pedagogical Institute in the system of relations “teacher-student.” The main objectives of this work are substantiation of the style of the teacher’s activity in the system of “teacher-student” relations from a socio-psychological point of view as a scientific and practical problem, as well as identifying the current state of the communication style, conducting chronometric observations of the communication methods of teachers in the classroom, studying the personal qualities of teachers, and comparing the results of the study depending on the gender and length of service of teachers, which will be analyzed in this paper. The article deeply covers the problem of organizing communication in the classroom aimed at learning Oriental languages, characterizes communication styles according to the Flanders observation scheme, and analyzes the activities of the teacher in the lesson from the point of view of a communicative approach to learning. A special emphasis was also placed on the specifics of interpersonal relationships between teachers and students when building the educational process, determining teaching styles, and identifying the most relevant style that gives the best result when students study foreign (Oriental) languages.